GAYA HIDUP THIRFTING DI PASAR LERENG BUKITTINGGI : STUDI KHASUS MOTIVASI FASHION DAN KEPUASAN ANAK MUDA - Elviriani Br Sitepu; Basyarul Aziz; Esa Rahmadani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The thrifting phenomenon at Pasar Lereng Bukittinggi has undergone a shift in meaning, from a mere economic solution to a lifestyle representing the social identity and creativity of young people. This study aims to analyze fashion motivation and consumer satisfaction among youth (specifically university students and Gen Z) through second-hand clothing consumption. Using a descriptive qualitative method, data were collected through observation and in-depth interviews with six informants, including traders and active consumers. The analysis employed three Contemporary Anthropology theories: Georg Simmel's Fashion theory to dissect identity motivation, Arjun Appadurai’s "Social Life of Things" to examine the re-commodification process of second-hand goods, and Daniel Miller’s Materiality theory to understand the impact of consumption on psychological wellbeing. The results indicate that thrifting serves as a means for young people to balance the desire for uniqueness (individuality) while staying relevant to global trends (conformity). Consumer satisfaction stems not only from owning branded items at affordable prices but also from the emotional experience of "the thrill of the hunt," which provides a sense of pride and inner happiness.